RITUALS OF JEKNEK SAPPARA CULTURE (BATH OF SAFAR) IN THE VILLAGE OF BARANGLOE, DISTRICT TAROANG, JENEPONTO REGENCY: A SEMIOTIC ANALYSIS - Nurul Fitrah Yani (International Journal of Malay-Nusantara Studies, 2018)
Thisqualitative descriptive study semiotically discusses the forms –word, phrase and sentence - and meanings of symbols in the ritual of "Akjeknek-Jeknek Sappara" in the village of Balangloe sub-district of Taroang, Jeneponto Regency. Data were collected by recording and notetaking the rituals and interview the elderly people. This study showed thatthere are some forms of ritual in traditional ceremony "Jeknek Sappara" with their meanings contained in theritual. The results of this research are expected to be one of the reference materials on the cultures of the indigenous peoples in the Jeneponto Regency.